SELF-EVALUATION OF PHYSICAL EDUCATION TEACHERS' HEALTH AS A FACTOR FOR QUALITY OF PROFESSIONAL ACTIVITIES - Kardeliene, Laimute; Razbadauskas, Arturas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Physical education teacher, as a profession, has various duties, which impact teacher's physical and emotional health. This may have an effect on quality of lessons. The aim of the research is to establish the self-evaluation of PE teachers' health. The following indicators of health self-evaluation were chosen: taking care of one's health, health condition and its evaluation. Questionnaires were used to self-evaluate PE teachers' health, to point out diseases such as having a cold, also various somatic and psychosomatic disorders. The sample of the research was 324 PE teachers, randomly chosen from high schools in Lithuania. The average age of the participants was 44,59 ± 0,57 years old, their pedagogical work experience - 20,52 ± 0,58 years. It was found that only 29,1 per cent of female and 18,3 per cent of male participants rated their health as good. Teachers who evaluated their health positively more seldom experienced various somatic and psychosomatic disorders. Teachers with more than 20 years of work experience rarely evaluated their health as good. In addition, they more frequently experienced various disorders.Women, when compared to men, are more prone to health disorders. Furthermore, women with more than 20 years of work experience more rarely fell into the group of long-term somatic and psychosomatic disorders.